Late effects and healthcare needs of survivors of allogeneic stem cell transplantation: a qualitative study. Issue 4 (2nd August 2012) - Hwang, Jessica P; Roundtree, Aimee K; Giralt, Sergio A; Suarez-Almazor, Maria
Abstract : Purpose: This qualitative study of survivors of allogeneic stem cell transplantation (SCT) for haematological malignancy explored attitudes about late effects of therapy, healthcare issues and information needs. Methods: We conducted 12 indepth cognitive interviews and three focus groups of patients who had previously had SCT and were without recurrence of their primary disease. We used grounded theory methods, where themes emerged from consensus between cocoders. Health-related quality of life was assessed with the short-form 36 (SF-36). Results: The study included 22 patients (50% female; 95% white; mean age 47 years). The mean time from SCT was 5.2 years (±1.4 years). Most had low SF-36 scores. Participants discussed late effects of therapy, most commonly graft-versus-host disease, and how they impacted their quality of life. They reported frequent healthcare use and cancer screening after SCT and discussed problems affording care and interacting with insurance companies. Participants shared sources of health information (eg, preferring providers as their primary sources of information, but also learnt from websites, medical journals and peer experiences) and identified information barriers (eg, feeling 'on their own' insofar as they did not have targeted care for their needs), and expressed importance of anticipatory guidance regarding infertility. Overall, participants' personal issues and social influences impacted survivors' needs and attitudes. Conclusions: SCT survivors face continuing and lasting health effects. The factors impacting survivorship needs are complex and may be interrelated. Future research should study the affect of incorporating personal and social issues into existing clinical SCT programmes on survivors' quality of life.